Phase and valence transitions in Ba2LnSnxSb1-xO6-δ (Ln=Pr and Tb) - Saines, P; Kennedy, B; Elcombe, M; Harris, H; Jang, L; Zhang, Z (2008)
Compounds in the double perovskites series Ba2LnSnxSb1-xO6-δ (Ln=Pr and Tb) have been synthesised and structurally characterised using synchrotron X-ray and neutron powder diffraction. It was found that the two end-members of the Ba2PrSnxSb1-xO6-δ series both adopt rhombohedral symmetry but the antimonate is a fully ordered double perovskite while the stannate has no B-site cation ordering. X-ray absorption near-edge structure (XANES) and near-infrared spectroscopy indicate that the Pr cations gradually change oxidation state from Pr3+ to Pr4+ with increasing x and that this is likely to be the cause of the loss of B-site ordering. Similarly, both Ba2TbSbO6 and Ba2TbSnO6-δ are cubic with B-site ordering present in the former but absent in the latter due to the oxidation state change of the Tb from Tb3+ to Tb4+. Multiple linear regression analysis of the Pr and Tb LIII-edge XANES indicates that the rate of Ln3+ transforming to Ln4+ is such that there are no oxygen vacancies in Ba2PrSnxSb1-xO6-δ but in Ba2TbSnxSb1-xO6-δ there is a small amount of oxygen vacancies, with a maximum of δ≈0.05 present. Crown Copyright © 2008.